Stripping voltammetric methods for the detemination of aflatoxin compounds [electronic resource] - 411827 Mohamad Hadzri Yaacob; Abdull Rahim Mohd. Yusoff; Universiti Teknologi Malaysia. Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (PhD) - Universiti Teknologi Malaysia, 2006